Musa spp. - Functional properties, biofortification, and bioavailability - Borges, C. V.; Maraschin, M. (My University, 2016)
Studies towards the identification and use of Musa spp. genotypes with functional properties have been conducted in connection with genetic breeding programs aiming at the optimization of nutritional characteristics of the fruit for mitigating certain pathophysiologies such as hypovitaminosis A. The results indicate the existence of an important chemodiversity associated with the genotypes of Musa spp, with substantial amounts of bioactive compounds in accessions non-cultivated extensively, compared to the commercially available cultivars. WHO (World Health Organization) data indicate hypovitaminosis A as a major nutritional problem in developing countries. To this end, metabolomic studies of Musa spp. fruit are of importance for the selection of genotypes with higher bioactive contents, e.g., pro-vitamin A carotenoids, as a strategy for biofortified cultivars development, with virtual application in programs of eradication of nutritional needs of less-favored socioeconomical populations. In this context, this review addresses the biochemical characterization of Musa spp. genotypes, with emphasis on bioactive secondary metabolites of interest to human nutrition. In addition, the bioavailability of pro-vitamin A activity compounds of banana fruits is reviewed, in association with the use of those biomasses in programs to overcome nutritional deficits of that vitamin and its clinical complications.